2003
DOI: 10.1076/phbi.41.5.379.15934
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Supercritical CO2 Extracts of Helichrysum italicum

Abstract: The antioxidant activity of supercritical CO2 extracts of H.\ud italicum dried flower heads derived from the commercial drug\ud and from plants grown in different areas of north-east Italy\ud with different culturing conditions was determined. In particular,\ud the characterization of the antioxidant activity was made by the DPPH and b-carotene bleaching test methods. The four kind of H. italicum extracts were also tested for their ability to scavenger superoxide radicals. All extracts showed, although with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 11 publications
1
23
0
1
Order By: Relevance
“…They were selected for their different characteristics. In fact, the DPPH test is particularly suitable for the evaluation of antioxidant activity of crude extracts (Poli et al, 2003), while the ABTS one is usually applicable also to biological tissues (Re et al, 1999).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…They were selected for their different characteristics. In fact, the DPPH test is particularly suitable for the evaluation of antioxidant activity of crude extracts (Poli et al, 2003), while the ABTS one is usually applicable also to biological tissues (Re et al, 1999).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Free-radical scavenging activity of the extracts was determined using a method based on the reduction of a methanolic solution of the colour-free radical DPPH (1,1-diphenyl-2-picrylhydrazyl) (Wang et al, 1998), modified as reported in Poli et al (2003). The activity was also calculated as IC 50 , which is the concentration (milligrams per millilitre) that inhibited 50% of the activity of the DPPH.…”
Section: Antioxidant Activity Procedures 341 Dpph Methodsmentioning
confidence: 99%
“…The test procedure used was similar to the one described by Taga et al [17] modified as reported in Poli et al [16]. All determinations were performed in triplicate and averaged.…”
Section: Determination Of the Antioxidant Activitymentioning
confidence: 99%
“…DPPH method. Free radical scavenging activity of the extracts was determined using a method based on the reduction of a methanolic solution of the colour free radical DPPH (1,1-diphenyl-2-picrylhydrazyl) [15] modified as reported in Poli et al [16]. The activity was calculated also as IC 50 ¼ concentration (mg mL À1 ) that inhibited the 50% of the activity of DPPH.…”
Section: Determination Of the Antioxidant Activitymentioning
confidence: 99%